Principles of Business Valuation - Brukštaitienė, Daiva; Eiva, Saulius (Ekonomika, 1999)
The article analyses business valuation theoretical methodologies and their application to Lithuanian environment. Authors poses clear distinction between methods used in practice and methods having scientific value, which are based more on indept business analyses and usage of mathematical methods. After having analysed different valuation methods, the authors have proposed to use Component Discounted Cash Flow in valuation of big local enterprises.In the article authors has revealed main problems, connected to Discounted cash flow method. Article covers calculation of discount rate, based on Weighted Average Cost of Capital and proposes concrete ways how to deal with it, as WACC is the main blocking factor of usage of Discounted Cash Flow valuation in Lithuania and Eastern Europe.